Trastorno de estrés postraumático en personas diagnosticadas de Covid-19 en el barrio Motupe periodo 2022 - Quizhpe Lozano, Cristian Fernando (2023)
The Covid-19 disease in addition to affect the physical health of the worldwide population, has produced an undermining in the mental health of those who suffer from it, rapidly expanding the rate of psychological disorders in moderate and severe forms, being one of the most frequent during and after outbreaks of the virus the Post Traumatic Stress Disorder, which manifest themselves after having a situation of high stress or trauma, such as getting seriously ill, being a victim of violence, traffic accidents or natural disasters, the most common symptoms are: sleeping problems, mood swings, intrusive memories, affective blunting and feeling of constant threat, directly affecting the normal functioning and health of a certain part of the population after being diagnosed with respiratory pathology. Therefore, the present research work had the objective of establishing the prevalence of post-traumatic stress disorder in people diagnosed with Covid-19 in the Motupe neighborhood, period 2022. It was a non-experimental quantitative design of transversal cut, descriptive and exploratory type, it was carried out in the Motupe neighborhood, located in Loja city, with a non-probabilistic sample of 81 participants between 18 and 75 years old. The results were obtained through the application of Global Post-traumatic Stress Evaluation - 5, it was found that there is a prevalence of post-traumatic stress disorder in 22.2%. As a measure of action, a prevention and intervention plan focused on the treatment of mental illness was designed